(3QSGdI aj JMbjb EbGeI GdMOhOs - (3eMeO HGbQ Hf eMeO Jbj GdCUagGfjs
(3ChdgG (B:s
... (3ajeG EPG MUd eYQaI GdeMOhO ef ZjQ WQjb GdJYQja ceG dG jNai Ydi GdeJCed hbGd GdaGVd GdGSJQGHGPj aj BjGJ GdCMcGe hgh YbhHI bO YjfgG GdTGQY Ydi cHjQI RLQG YfgG hajg eG YQaJ (B...s
(3BNQgG (B:s
... (3JHjf Cf LhRG EbGeI GdMOhO aj gPg GdCYUGQ ddabgGA eOdhd Ydjg HeG jXgQ ef GWHGb YdeGA GdWGFaI hYeheGJ GdcJGH hGdSfI hNUhU GdQhGjI GdSGdaI Cj bhdg ef GbGeI GdMOhO (B... (3addg GdMeOs
(3Jdjg QSGdI HGdaGQSjIs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3abg GdePGgH GdCNQis